Slide Wear Resistance of Electric Traction Cables - Bangshidhar Goswami,; Saroj Dutta, Tridib Kumar Pathak, Indira Singha, Nupur Goswami, Bhakti Bharati Mishra, Tarun Kumar Goswami, Deep Sen, Jaydev Banerjee, (Journal of Electronic Design Engineering, 2021)
The study has been to explain electrical sliding wear conditional behaviour and wear mechanism of various age-hardened copper-based alloys. The scheme has delineated the corrosion behaviour of alloys in 3.5% NaCl solution. Thus, optimization criteria of overhead line/pantograph systems have been designed to assure high-speed contact lines. Extrapolation of result has succeeded designation to apply high strength contact wire materials, e.g., CuMg alloy after addition of Re330. Extended ethical has procured metalized pantograph slipper materials yet the variation of atmospheric conditions. Technical developments have meant to subject electric railways with a speedup of train and reduction of cost to maintain facilities from the forefront of innovation. Relevance decisive has been dedicated to meeting the expectations of people. In lieu, contact wire has been one of the criteria studied to speed up the train and reduce the cost of maintenance. Quality of contact wire has improved after the addition of new materials/alloy in response to low wear rate and suit an addendum combination of high strength and high conductivity. High-speed electrified railway traffic has evolved in lieu, Cu–Ag–Cr alloy to be another kind of improved contact wire material. Wear mechanisms between contact wire made of Cu–Ag–Cr alloy and strips have been studied to carry out slide wear behaviour using a specific slide wear tester. Copper-based powder metallurgy strip has used as contact strip on pantograph of electric railway vehicle in train system that has scheduled to slide against Cu–Ag–Cr alloy wire, henceforth wear mechanism of wire has scriptive issued. Ad-hoc wear resistance of Cu–Ag–Cr alloy contact wire has compared with Cu–Ag alloy contact wire under same testing conditions.